Assessing Zambia's industrial fortification options: Getting beyond changes in prevalence and cost-effectiveness - Fiedler, John L.; Lividini, Keith; Kabaghe, Gladys; Zulu, Rodah; Tehinse, John; Bermudez, Odilia I.; Jallier, Vincent; Guyondet, Christophe (SAGE Publications, 2013)
Since fortification of sugar with vitamin A was mandated in 1998, Zambia's fortification program has not changed, while the country remains plagued by high rates of micronutrient deficiencies.To provide evidence-based fortification options with the hope of reinvigorating the Zambian fortification program.Zambia's 2006 Living Conditions Monitoring Survey is used to estimate the apparent intakes of vitamin A, iron, and zinc, as well as the apparent consumption levels and coverage of four fortification vehicles. Fourteen alternative food fortification portfolios are modeled, and their costs, impacts, average cost-effectiveness, and incremental cost-effectiveness are calculated using three alternative impact measures.Alternative impact measures result in different rank orderings of the portfolios. The most cost-effective portfolio is vegetable oil, which has a cost per disability-adjusted life-year (DALY) saved ranging from 12% to 25% of that of sugar, depending on the impact measure used. The public health impact of fortified vegetable oil, however, is relatively modest. Additional criteria beyond cost-effectiveness are introduced and used to rank order the portfolios. The size of the public health impact, the total cost, and the incremental cost-effectiveness of phasing in multiple vehicle portfolios over time are analyzed.Assessing fortification portfolios by measuring changes in the prevalence of inadequate intakes underestimates impact. A more sensitive measure, which also takes into account change in the Estimated Average Requirement (EAR) gap, is provided by a dose—response-based approach to estimating the number of DALYs saved. There exist highly cost-effective fortification intervention portfolios with substantial public health impacts and variable price tags that could help improve Zambians' nutrition status.